2020
DOI: 10.1007/s40368-020-00548-4
|View full text |Cite
|
Sign up to set email alerts
|

General dental practitioners’ approach to caries prevention in high-caries-risk children

Abstract: Aims To evaluate the advice and preventive care provided by General Dental Practitioners (GDPs) to high-caries-risk children in Jordan. Methods A cross-sectional study using an open-ended questionnaire. GDPs were presented with a high-caries-risk child scenario and asked regarding: (1) oral hygiene and dietary advice they would give; (2) preventive-care they would offer; (3) barriers they face in prevention delivery. Answers were compared to an evidence-based guideline. Data were input into SPSS-20 and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In a previous study, dentists cited parental motivation as a key barrier to preventive care delivery [28]. This underlines the importance of involving parents 'directly' in future oral health promotion efforts.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous study, dentists cited parental motivation as a key barrier to preventive care delivery [28]. This underlines the importance of involving parents 'directly' in future oral health promotion efforts.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, all children aged six or younger can receive dental care for free at public centres and hospitals. Dentists in Jordan previously indicated that they feel that parental motivation is the most important factor in providing dental care for children [ 33 ]. It is important that future oral health promotion encourages regular attendance every three to six months, as recommended for children in this age group, and that we continue to explore barriers to access of dental care and how those can be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Those preventive treatments are recommended by various organisations and have proven their effectiveness in caries prevention [ 34 , 35 ]. In a previous study, dentists in Jordan indicated that these treatments are available but highlighted parental motivation as a crucial factor in patient selection [ 33 ]. Raising public awareness about the benefits of these treatments is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Considering dentists, studies also indicate that their daily practices do not strongly emphasize prevention. Practitioners report spending little time on patient education, which usually consists of brief generalist advice [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%